2022
DOI: 10.5540/tcam.2022.023.04.00625
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Linear Long Water Waves over Variable Topographies using a Conformal Mapping

Abstract: In this work we present a numerical study of surface water waves over  variable topographies for the linear Euler equations based on a conformal mapping and Fourier transform. We show that in the shallow-water limit the Jacobian of the conformal mapping brings all the topographic effects from the bottom to the free surface. Implementation of the numerical method is illustrated by a MATLAB program. The numerical results are validated by comparing  them with exact solutions when the bottom topography is flat, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…These results ties with the study of Nachbin and Solna [20]. We notice that the changing in the dynamic presented in this work is different from the ones reported by Flamarion and Ribeiro-Jr [11]. In this article, the authors showed that a monochromatic rapidly varying topography barely affects the shape of the pulse, while a slowly varying topography causes a considerable variation in amplitude and an increasing of reflected waves.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…These results ties with the study of Nachbin and Solna [20]. We notice that the changing in the dynamic presented in this work is different from the ones reported by Flamarion and Ribeiro-Jr [11]. In this article, the authors showed that a monochromatic rapidly varying topography barely affects the shape of the pulse, while a slowly varying topography causes a considerable variation in amplitude and an increasing of reflected waves.…”
Section: Resultssupporting
confidence: 78%
“…In this article, the authors showed that a monochromatic rapidly varying topography barely affects the shape of the pulse, while a slowly varying topography causes a considerable variation in amplitude and an increasing of reflected waves. This occurs because only monochromatic topographies are considered in [11]. Therefore, our study shows that when the topography is modeled by a series of Fourier modes the wave field changes considerably.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations